1987
DOI: 10.1038/327535a0
|View full text |Cite
|
Sign up to set email alerts
|

Optically active benzo[c]phenanthrene diol epoxides bind extensively to adenine in DNA

Abstract: Reactions of diol epoxide metabolites of carcinogenic polycyclic aromatic hydrocarbons with DNA are thought to initiate the carcinogenic process. Although formation of a benzo[a]pyrene (BaP) diol epoxide-deoxyguanosine adduct has been held responsible for biological activity, the more potent carcinogen, 7,12-dimethylbenz[a]anthracene (DMBA) binds extensively to deoxyadenosine residues in DNA, suggesting that hydrocarbon carcinogen-deoxyadenosine adducts may be instrumental in tumour initiation. Because the bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
170
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(185 citation statements)
references
References 0 publications
15
170
0
Order By: Relevance
“…4). Similarly, BcPHDE is an aromatic hydrocarbon that can form adducts with A or G (7,22). The action of this mutagen has been studied at the dhfr locus in CHO cells; both A and G were targets, with a great preference for the 5' base of di-or tripurine sequences (13).…”
Section: Resultsmentioning
confidence: 99%
“…4). Similarly, BcPHDE is an aromatic hydrocarbon that can form adducts with A or G (7,22). The action of this mutagen has been studied at the dhfr locus in CHO cells; both A and G were targets, with a great preference for the 5' base of di-or tripurine sequences (13).…”
Section: Resultsmentioning
confidence: 99%
“…For example, (-)-BcPhDE-1 is essentially devoid of tumorigenic activity, whereas (-)-BcPhDE-2 is the most active hydrocarbon dihydrodiol epoxide tested to date, and the other stereoisomers exhibit intermediate activities (12). To investigate the basis for these tumorigenic activities, relative mutagenicities in bacterial and mammalian cells have been reported (13), as have detailed studies of the chemistry of their interactions with DNA (14,15). These studies have shown that the exocyclic amino groups of deoxyadenosine and deoxyguanosine are the principal sites of reaction and that opening of the dihydrodiol epoxide occurs both cis and trans at the benzylic position.…”
mentioning
confidence: 99%
“…Other planar PAH diol-epoxides that contain a bay or fjord region, such as benz [a]anthracene and chrysene, bind covalently and almost exclusively with guanine bases in DNA. By contrast, the fjord region diol-epoxides of benzo[c]phenanthrene, with a distortion from the planarity of the parent molecule, react with adenine and guanine bases in DNA (Dipple et al, 1987;Jerina et al, 1991). The poorly repaired DNA adducts can persist until replication and cause mutations (Smith et al, 2000;Feng et al, 2002;Rodríguez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%